De same ole Huck – America’s speculum meditantis. A (p)re-view - Semrau, Janusz (Adam Mickiewicz University, 2006)
By common agreement, Huckleberry Finn is not only the most American boy in literature, but is also the character with whom American readers of all ages tend to identify most readily and most intimately. Against ready-made assumptions, the paper investigates the protagonist’s unique constitution, modus operandi, and existential appeal. As a passe-partout to the text, it is suggested that Huck is at one and the same time, and as a primary rather than a secondary phenomenon, a small boy as well as a full-grown man. An apparent repository of classically definable unnecessary desires, informed by a combined Carlylean-Melvillean-Whitmanesque discourse of the (magical) mirror, Twain’s figure in the carpet emerges as a nuanced negotiation and transposition: speculum meditantis – mirror of one meditating, speculum vitae humanae – mirror of human life, speculum totis paria corporibus – mirror equal to the body of the country at large, and ultimately hyperbolically as utilitarian speculum humanae salvationis.